Long standing forearm dislocations - Matelenok, Ievgen (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Dislocations that remain unreduced for 3 weeks or more, are called the chronic elbow dislocation. Today they are found quite rarely. Objective: to study the probable causes of long standing forearm dislocations, to analyze medical tactics and results of treatment. Methods: we used the data of clinical observations of 5 patients (2 men, 3 women), mean age (38 ± 8) years with long standing forearm dislocations. All patients had surgical treatment. Results: the cause of the long standing dislocations occurrence, in 2 cases there was a violation of medical recommendations by patients, in 3 — insufficient medical control, absence of control radiography after immobilization, lack of timely correction of the patient’s management, erroneous the choice of conservative treatment tactics in the presence of indications for surgery. Features of treatment tactics depending on the characteristics of dislocations were analyzed. Comparative data of the joints function are given: the amplitude of flexion/extension movements before the surgery was 25° ± 6°, after — 108° ± 5°; assessment of the limb function according to Mayo Elbow Performance Index before the surgery was equal to (23 ± 5) points, in the follow-up period (17 ± 2) months) — (81 ± 7) points (p < 0.001). Conclusions: in the case of long standing posterior dislocations, open reduction of the forearm can be performed from the lateral approach with restoration of injuried ligaments, in the case of posterior-lateral — it is advisable to use posterior approach, which allows for more complete arthrolysis, tissue mobilization, restoration of ligaments, as well as perform neurolysis, transposition of the ulnar nerve. In case of short terms of long standing forearm dislocation it is possible to manage a temporary fixation of the joint with one or two wires, passed through the joint and external fixation with a plaster cast for a period of 15 up to 30 days with subsequent mobilization without the use of external fixation devices.